Introduction to mechanics - Kleppner, Daniel; Kolenkow, Robert J. (New Delhi: Tata McGraw Hill Pvt. Ltd., 2010)
An Introduction To Mechanics, by Robert J. Kolenkow and Daniel Kleppner, is a comprehensive elaboration of mechanics in the field of Physics. This book is primarily for the students of an undergraduate course in Physics. In this book, the basic concepts related to the mechanics of Physics are elaborated. The presentation makes it easy to understand from the standpoint of the student who has a general knowledge about calculus and fundamental mathematics.There are chapters based on important topics like kinetics, vectors, work and energy, central force motion, relativistic kinematics, angular momentum, fixed axis rotation, harmonic oscillator, the basics of newtonian mechanism, non-inertial systems, fictitious forces, rigid body motion, conservation of angular momentum, and many more to list down. There are over 700 illustrations to help the students understand better. Also, there are exercises segregated question-wise at the end of each chapter for the students to practice on the basis of their study.In addition to the conceptual text and question papers, there are a lot of solved examples to provide additional practice-support to the students. To gain the initial information about mechanics, this book is a good reference guide.
Index 539-546p.
Keywords: Mathematics; Mechanics; Newtons law; Vectors and kinematics; Physics